Relationship of stock prices, foreign exchange, interest rate, money supply and its Impact on portfolio performance in Indian and Chinese stock markets - Feng, Yanan (Animo Repository, 2015)
The study aims to find the relationship of stock prices, foreign exchange, interest rate, money supply and its impact on portfolio performance in Indian and Chinese stock markets by gather the data from 2001-2010 and use Augmented Dickey-Fuller unit root test, Fully Modified Ordinary Least Square and Autoregressive Distributed Las Model in Eviews. Based on the results, the stock prices positively affected by money supply in the long run and statistically significant with it. The foreign exchange rate is negatively affected by inflation and interest rate in the short run, and insignificantly associated with the money supply in the long run. The money supply has positive relationship with economic activity, but negative relationship with interest rate, and it shows a phenomenon of periodic fluctuation. Since the volatility of money supply leads the stock prices, so once the money supply comes with the periodic high point, so followed by the high point for stock prices and the inflation. The investors can use the model of this study to forecast the best point to invest for China and India base on the historical data.